2018
DOI: 10.1063/1.5050021
|View full text |Cite
|
Sign up to set email alerts
|

Torsional splitting and the four-fold barrier to internal rotation: The rotational spectra of vinylsulfur pentafluoride

Abstract: Vinylsulfur pentafluoride (VSPF), a molecule with a four-fold internal rotor, —SF4, has been studied with high resolution Fourier transform microwave spectroscopy. We believe that this is the first report of resolved four-fold internal rotation. As such, we have presented the tools needed to understand and analyze such a problem. These include debugging the ERHAM computer program necessary to fit the spectra and the free rotor to high barrier correlation diagram necessary to understand the torsional states of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…1 Methyl torsion is regarded as a well understood LAM, 2 with the number of papers reporting the analysis of microwave spectra for molecules containing a methyl group recently being estimated to exceed 1000. 3 Microwave studies observe transitions between rotational states rather than observing the transitions between the torsional states directly but, nonetheless, constants describing the torsional motion, particularly the torsional potential, can be determined when fitting the observed line positions. 2,[4][5][6][7] Although there are many fewer studies of methyl torsion using electronic spectroscopy, studies of supersonically cooled gas phase samples have allowed torsional states to be observed directly (see Ito 8 and Breen et al 9 for early examples).…”
Section: Introductionmentioning
confidence: 99%
“…1 Methyl torsion is regarded as a well understood LAM, 2 with the number of papers reporting the analysis of microwave spectra for molecules containing a methyl group recently being estimated to exceed 1000. 3 Microwave studies observe transitions between rotational states rather than observing the transitions between the torsional states directly but, nonetheless, constants describing the torsional motion, particularly the torsional potential, can be determined when fitting the observed line positions. 2,[4][5][6][7] Although there are many fewer studies of methyl torsion using electronic spectroscopy, studies of supersonically cooled gas phase samples have allowed torsional states to be observed directly (see Ito 8 and Breen et al 9 for early examples).…”
Section: Introductionmentioning
confidence: 99%